Teaching Learning Process Of Extracurricular SpeakingClass At Smp Muhammadiyah 10 Surakarta In 2015/2016Academic Year A Naturalistic Study - Santoso, Kurniawan Budi; , Prof. Dr. Endang Fauziati,M.Hum (2016)
Kurniawan Budi Santoso. A320120058. TEACHING LEARNING PROCESS OF EXTRACURRICULLAR SPEAKING CLASS AT SMP MUHAMMADIYAH 10 SURAKARTA: A NATURALISTIC STUDY. Research Paper. Muhammadiyah University of Surakarta, 2016. The purpose of this study to carry out is to describe the teaching learning process of extracurricular speaking class at SMP Muhammadiyah 10 Surakarta. The kind of this research is a descriptive qualitative study especially naturalistic study in analyzing the data. The method used in this study are observation, interviews and document analysis. The findings of this study show that the learning objectives at SMP Muhammadiyah 10 Surakarta is divided into two: general objective and specific objective. The general objective is communicative efficiency, while the specific objective,especially the students are able speak English well in immediate environment. The types of classroom technique are discussion, question and answer, role playing and jigsaw. The classroom procedure is using 5E (Engagement, Exploration, Explanation, Elaboration, Evaluation). There are two types of classroom interaction: interaction between the teacher and students and interaction between the student with other students. The roles of the teacher is the teacher as a manager, teacher as facilitator, the teacher as the instructor, the teacher as motivator and teacher as evaluator. While the student's role is as an active participant and member of the group. Media used in the study is the whiteboard, markers, audio, video, laptop and LCD. Assessmet used by the teacher are homework, oral tests and daily activities. Keyword: teaching and learning, extra